Assessing the Compliance of Pantawid Pamilya Pilipino Program Beneficiaries with Health Conditionalities: A Descriptive Study - Joyzel Rey E. Garcia (Journal of Social Sciences and Management Studies, 2025)
This study explored the extent of compliance of Pantawid Pamilya Pilipino Program (4Ps) beneficiaries with health-related conditionalities in La Carlota City. Utilizing a descriptive research design, the study employed both qualitative and quantitative methods to systematically collect and analyze data, allowing for a comprehensive understanding of compliance patterns (Bueno, 2016). This methodological approach proved effective in achieving the research objective of gathering factual and actionable information about beneficiary adherence to program conditions. The findings highlight the degree to which health-related requirements of the 4Ps are met by beneficiaries, shedding light on factors that facilitate or hinder compliance. The study's results provide evidence-based insights for program implementers and policymakers to strengthen health-related components of the 4Ps and enhance overall program effectiveness. The descriptive research design was deemed most appropriate for this inquiry, demonstrating its utility in addressing research questions that require both qualitative depth and quantitative precision.